2008
DOI: 10.4315/0362-028x-71.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Direct-Fed Microbials on Fecal Shedding of Escherichia coli O157:H7 and Salmonella in Naturally Infected Feedlot Cattle

Abstract: The effect of direct-fed microbials (DFM) on fecal shedding of Escherichia coli O157:H7 and Salmonella in naturally infected feedlot cattle was evaluated in a clinical trial involving 138 feedlot steers. Following standard laboratory methods, fecal samples collected from steers were evaluated for change in the detectable levels of E. coli O157:H7 and Salmonella shed in feces after DFM treatment. Sampling of steers was carried out every 3 weeks for 84 days. A significant reduction (32%) in fecal shedding of E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 28 publications
1
25
1
1
Order By: Relevance
“…S. cerevisiae I-1077 has also been shown to affect the growth and activities of rumen microbial communities (14), so STEC inhibition could also be associated with a modified balance of the resident microbiota. L. acidophilus BT-1386 has been reported to limit the prevalence of O157:H7 in naturally infected feedlot cattle (40), and it inhibits the in vitro growth of E. coli O157:H7 in fecal suspensions (13). In this study, we found high concentrations of lactate in the rumen contents incubated with L. acidophilus, which presumably led to the observed decrease in pH.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…S. cerevisiae I-1077 has also been shown to affect the growth and activities of rumen microbial communities (14), so STEC inhibition could also be associated with a modified balance of the resident microbiota. L. acidophilus BT-1386 has been reported to limit the prevalence of O157:H7 in naturally infected feedlot cattle (40), and it inhibits the in vitro growth of E. coli O157:H7 in fecal suspensions (13). In this study, we found high concentrations of lactate in the rumen contents incubated with L. acidophilus, which presumably led to the observed decrease in pH.…”
Section: Discussionsupporting
confidence: 49%
“…Several studies have demonstrated the capacity of certain lactic acid bacteria or yeast to reduce E. coli O157:H7 counts in vitro (1,34) or in vivo (5,40). The mechanisms of action of probiotics are not well characterized but could involve competition for nutrients and adhesion sites in the GIT, an increase in the VFA concentration and a decrease in the pH, production of antimicrobial molecules, or interference with quorum-sensing signaling (27)(28)(29).…”
mentioning
confidence: 99%
“…Some organisms could be direct competitors by occupying the same niche, whereas others might have antagonistic or predatory activities. Isolation and identification of microorganisms that promote the decline of the invader may pinpoint inhibitory species, which might be applied as probiotics to reduce the survivability of pathogenic E. coli (Tabe et al, 2008). Conversely, the presence of cellulose-and lignindegrading organisms might provide E. coli with easily available carbon sources.…”
Section: Presence and Diversity Of An Indigenous Microfloramentioning
confidence: 99%
“…Probiotics exert beneficial effects on the host by providing nutrients and enzymatic contribution to digestion, improving water quality, enhancing growth, inhibiting pathogenic microorganisms and enhancing immune responses (Balcazar et al, 2006;Verschuere et al, 2000). The supplementation of Lactic Acid Bacteria (LAB) as probiotics in ruminants has been extensively studied as compared with Bacillus probiotics (Brashears et al, 2003;Maragkoudakis et al, 2010;Peterson et al, 2007;Tabe et al, 2008;Younts-Dahl et al, 2004). However there are very few reports on cellulolytic activities of LAB.…”
Section: Introductionmentioning
confidence: 99%